Analytical models for functionally graded adhesive single lap joints: A comparative study. (July 2017) - Stein, N.; Felger, J.; Becker, W.
Abstract: Functionally graded adhesives yielding a varying adhesive Young's modulus along the overlap are increasingly considered in order to allow for a more uniform stress distribution and to reduce the occuring stress concentrations in the adhesive layer of adhesively bonded single lap joints. The present work provides a comparative study of the existing analytical models for planar functionally graded adhesive single lap joints. The respective modelling assumptions as well as the conditions of applicability of the different approaches are examined in detail. In addition, a novel approach and possible extensions of the presented approaches are outlined and discussed. A thorough comparative study comprising various single lap joint configurations and adhesive Young's modulus distributions along the overlap is performed in order to assist the engineer choosing the adequate model for a particular single lap joint design. For an assessment of the accuracy, the calculated adhesive stress fields are compared to numerical results obtained by Finite Element Analyses. In addition, the effects of the adhesive Young's modulus range on the peak adhesive stresses are studied and discussed.